Prevalencia y factores asociados con el consumo diario de cigarrillo en mujeres adultas de Bucaramanga, Colombia Prevalence and factors associated with daily cigarette smoking amongst adult women in Bucaramanga, Colombia - Adalberto Campo-Arias; Luis Alfonso Díaz-Martínez (Federación Colombiana de Obstetricia y Ginecología, 2006)
Objetivo: el consumo de cigarrillo es un problema de salud pública que crece gradualmente en mujeres y se asocia con una importante morbimortalidad. El objetivo de este estudio fue hallar la prevalencia y los factores asociados con el consumo diario de cigarrillo en mujeres adultas. Diseño: estudio poblacional transversal. Lugar: población general de la ciudad de Bucaramanga, Colombia. Participantes: mujeres adultas letradas entre 18 y 65 años de edad. Intervenciones: ninguna. Principales resultados a medir: consumo diario de café, consumo abusivo de alcohol, trastornos mentales comunes y consumo diario de cigarrillo durante el último mes. Resultados: se entrevistaron 1.726 mujeres con edad promedio de 38,3 años (DE=13,3) y escolaridad promedio de 8,8 años (DE=3,9); 56,2% estaban casadas; 37,1% eran empleadas; 68% residían en estrato medio; 44,4% consumía diariamente café; 1,4% presentaba consumo abusivo de alcohol; y 15,8% informó un trastorno mental común. La prevalencia de fumadoras actuales fue 6,3% (IC95% 5,2-7,4). Luego de controlar por escolaridad, el consumo diario de cigarrillo se asoció con el consumo abusivo de alcohol (OR=5,1; IC95% 2,0-12,8; p=0,001); la presencia de un trastorno mental común (OR=3,5; IC95% 2,2-5,3; p<0,001), el consumo diario de café (OR=3,0; IC95% 1,9-4,6; p<0,001) y vivir en estrato socioeconómico bajo (OR=1,5; IC95% 1,0-2,4; p=0,042). Conclusiones: una de cada dieciséis mujeres de la población general consume cigarrillo diariamente. Es necesaria la promoción activa del abandono de este consumo en esta población. Objective: cigarette smoking is increasing becoming a public health problem for women and is related to important morbidity and mortality. This research was aimed at establishing the prevalence of and factors associated with daily cigarette smoking in adult women. Design: a cross-sectional, population-based study. Setting: the general population of Bucaramanga, Colombia. Participants: literate adult women aged 18 to 65. Interventions: none. Mean outcome measures: daily caffeine drinking, abusive alcohol consumption, common mental disorders, and the last-month daily cigarette smoking. Results: 1,737 women were interviewed. Their mean age was 38.3 years (SD=13.3) and they had had an average of 8.8 years schooling (SD=3.9). 56.2% of the women were married, 37.1% were employees, 68.0% were living in middle-class neighbourhoods, 44.4% drank caffeine everyday, 1.4% reported abusive alcohol consumption, 15.8% presented a common mental disorder and 17.6% had a known medical condition. There was 6.3% cigarette smoking prevalence (5.2-7.4 95%CI). After controlling for educational level, daily cigarette smoking was associated with abusive alcohol consumption (OR=5.1; 2.0-12.8 95%CI; p=0.001), presenting a common mental disorder (OR=3.5; 2.2-5.3 95%CI; p<0.001), daily caffeine drinking (OR=3.0; 1.9-4.6 95%CI; p<0.001) and living in neighbourhoods having low socioeconomic status (OR=1.5; 1.0-2.4 95%CI; p=0.042). Conclusions: one out of sixteen women from the general population smokes everyday. Actively promoting quitting smoking in this population has thus become most important.